POSTMODERN THEATRE AND RESISTANCE: A CATALYST FOR TRANSFORMATIVE EXPRESSION - Krishnan, Vineetha (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Postmodern feminist theatre in India redefines storytelling by integrating fragmented narratives, cultural hybridity, and active audience engagement to critique societal power structures. It amplifies marginalized voices through mythological reinterpretations, experimental performances, and community-driven initiatives. Themes of gender, caste, class, and identity intersect, fostering dialogue and activism. Embracing innovation, ecofeminism, and intersectionality, this dynamic genre continues to challenge patriarchy, inspire social change, and create inclusive spaces for resistance, dialogue, and empowerment. Unlike traditional theatre, which often relies on realism and imitating life (mimesis), postmodern theatre rejects these conventions, opting for abstract, fragmented, and non-linear narratives instead. This departure from the norm allows the medium to construct unique and thought-provoking representations that serve as powerful tools for social critique. In essence, postmodern theatre acts as a living canvas for resistance, fostering an environment where art, activism, and community intersect. It challenges traditional forms while offering an inclusive platform for exploring diverse perspectives, ultimately contributing to transformative social change. Indian postmodern theatre serves as a powerful platform for feminist expression, bringing to light themes that challenge patriarchal constructs and amplify marginalised voices. These themes, rooted in the complexities of identity, culture, and resistance, redefine the role of theatre as a medium for socio-political critique and transformation.